Batch microfabrication and testing of a novel silicon-base miniaturized reference electrode with an ion-exchanging nanochannel array for nitrite determination. Issue 34 (25th June 2019) - Yin, Jiawen; Zhang, Wei; Zhang, Zan; Jin, Han; Gao, Wanlei; Jian, Jiawen; Jin, Qinghui
Abstract : In this paper, a miniaturized Ag/AgCl reference electrode, which can be mass-produced by micro–nano manufacturing technology, was developed and demonstrated to have good stability and a long lifetime. Abstract : The reference electrode (RE) provides a stable potential for electrochemical detection; therefore, the RE plays an important role in environmental monitoring. In this paper, a novel batch of microfabricated silicon-base miniaturized Ag/AgCl RE was reported. A specially designed mini-tank for saturated KCl solution storage and a nanochannel array for ion-exchange were fabricated on a 4 inch (100) silicon wafer using a two-step KOH anisotropic etching process. An Ag/AgCl electrode was fabricated on a 4 inch Pyrex 7740 glass substrate. Finally, the finished silicon and glass substrates were anode bonded to form the entire system. By comparing with a conventional solid-state Ag/AgCl RE in electrochemical microsensors, a pre-packaged saturated KCl solution in the mini-tank provided a stable working environment for the Ag/AgCl electrode to ensure a constant reference potential. Compared with a routine glass-structured RE and by replacing the ion-exchange membrane with a nanochannel array, the miniaturized RE achieved a longer lifetime. The size of the finished miniaturized RE electrode was 11 mm × 14 mm. The reference potential variation was only 0.1 mV under continuous testing for 3000 s. The standard deviation in the reference potential was only 1.314 mV in different Na2 SO4 buffer concentrations ranging from 3 mM to 30 mM. To verify the practicality of the novel silicon-base miniaturized RE, the fabricated RE was applied to measure the amount of nitrite in a water sample and achieved a better linearity of R 2 = 0.998. This miniaturized RE showed better reference potential stability and consistency because of the batch fabrication technique. This novel strategy for the design and manufacture of the miniaturized RE shows a bright future in the wide use of electrochemical sensors in online monitoring of water pollutants.